THE INFLUENCE OF THE JIGSAW TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS IN SOCIAL AT UPTD SMP NEGERI 12 PEMATANGSIANTAR - Vera Elisabet Siahaan; Tumpal Manahara Siahaan; Herlina Hotmadinar Sianipar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of the Jigsaw Type Cooperative Learning Model on student learning outcomes in Social Studies (IPS) for eighth-grade students at UPTD SMP Negeri 12 Pematangsiantar in the 2024/2025 academic year. The research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The sample was selected through purposive sampling: class VIII-4 as the experimental group using the Jigsaw Type Cooperative Learning Model, and class VIII-3 as the control group using the conventional (lecture) method, with 32 students in each class. The research instrument consisted of a multiple-choice test with 25 items, which had been tested for validity, reliability, difficulty level, and discriminating power. The validity test showed that all items were valid (r count > r table = 0.349), with the highest validity coefficient being 0.8019 and the lowest 0.3665. The instrument's reliability was 0.807 > 0.396, indicating that the test was reliable. The normality test indicated that both classes had normally distributed data (X² count < X² table), and the homogeneity test indicated that both groups were homogeneous (F count = 1.025 < F table = 1.804). The results showed that the experimental class had an average score of 80 with a standard deviation of 10.36, while the control class had an average score of 74.25 with a standard deviation of 10.10. The t-test revealed t count = 2.21 > t table = 1.67, indicating a significant difference in learning outcomes between the two classes. Therefore, it can be concluded that the Jigsaw Type Cooperative Learning Model has a significant influence on student learning outcomes in Social Studies and is more effective than the conventional method.